EDITORIAL - Editor (PINS-Psychology in Society, 2025)
The perennial theme of this Journal, namely the questioning and discussion of the relevance of psychological theories and practices in South Africa, emerges strongly in this issue. There has been an important shift in this debate in recent years, as the emphasis has moved from producing critiques of mainstream psychology to constructing (both theoretically and in practice) viable alternatives. Despite this shift and its important gains, the need for ongoing criticism remains. The hegemony within South African psychology has not been noticeably shaken in recent years and the alternative movements remain relatively weak in ’psychological politics’. Thus it is appropriate that this issue of Psychology in Society includes both examinations of possible new orders and practices in psychology and critiques of the mainstream.